Faktor-Faktor Yang Mempengaruhi Kepatuhan Hukum Masyarakat Dalam Membayar Pajak Kendaraan Bermotor di Kota Kupang - Apliana P. R. P. L. Zogara; Saryono Yohanes; Hernimus Ratu Udju (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
Motor Vehicle Tax, hereinafter abbreviated as PKB, is Tax on ownership and/or control of motorized vehicles and Regional Tax, hereinafter referred to as Tax, is a mandatory contribution to the Region that is owed by an individual or body that is coercive based on the Law without receiving direct compensation and used for regional needs for the greatest prosperity of the people. This type of research is Empirical Juridical research. The types and sources of data used are primary and secondary data. Primary data is data obtained directly from the research location through direct interviews with respondents and based on researcher observations. Secondary Data is data obtained from literature study. Data was analyzed descriptively qualitatively. The results of this research show that: (1) Factors that influence taxpayer compliance in paying motor vehicle taxes in Kupang City are: (a) Taxpayer compliance, (b) Tax rates, (c) tax sanctions (d) service quality. (2) Efforts made by the government to increase taxpayer legal compliance in paying motor vehicle tax in Kupang City are: (a) Expansion of motor vehicle tax payment channels, (b) Service approach to the community, (c) motor vehicle tax relief policy.